2014
DOI: 10.1002/adsc.201300784
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Synthesis of Medium‐Chain α,ω‐Dicarboxylic Acids and ω‐Aminocarboxylic Acids from Renewable Long‐Chain Fatty Acids

Abstract: Biotransformation of long‐chain fatty acids into medium‐chain α,ω‐dicarboxylic acids or ω‐aminocarboxylic acids could be achieved with biocatalysts. This study presents the production of α,ω‐dicarboxylic acids (e.g., C9, C11, C12, C13) and ω‐aminocarboxylic acids (e.g., C11, C12, C13) directly from fatty acids (e.g., oleic acid, ricinoleic acid, lesquerolic acid) using recombinant Escherichia coli‐based biocatalysts. ω‐Hydroxycarboxylic acids, which were produced from oxidative cleavage of fatty acids via enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
108
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(112 citation statements)
references
References 25 publications
1
108
0
3
Order By: Relevance
“…These oleate hydratases have in common, that they do not at all or only to a minor extent hydrate ∆12 double bonds in linoleic acid. Oh and coworkes, however, have identified a new ∆12-hydratase from Lactobacillus acidophilus, which predominantly forms the 13-hydroxy derivative of linoleic acid [133,134]. In addition, Hirata and coworkers showed that the ∆12-hydratase from Lactobacillus not only converts C18 cis PUFAs, but also arachidonic acid (C20) and DHA (C22) into the corresponding 15-hydroxy fatty acid and the14-hydroxy fatty acids, respectively [135].…”
Section: Fatty Acid Double Bond Hydratasesmentioning
confidence: 99%
See 2 more Smart Citations
“…These oleate hydratases have in common, that they do not at all or only to a minor extent hydrate ∆12 double bonds in linoleic acid. Oh and coworkes, however, have identified a new ∆12-hydratase from Lactobacillus acidophilus, which predominantly forms the 13-hydroxy derivative of linoleic acid [133,134]. In addition, Hirata and coworkers showed that the ∆12-hydratase from Lactobacillus not only converts C18 cis PUFAs, but also arachidonic acid (C20) and DHA (C22) into the corresponding 15-hydroxy fatty acid and the14-hydroxy fatty acids, respectively [135].…”
Section: Fatty Acid Double Bond Hydratasesmentioning
confidence: 99%
“…What is more, the importance of regiospecific biocatalytic hydration as key step for the production of high-value-added products like flavors, resins, waxes, nylons, plastics, lubricants, polymers etc. from fatty acids can well be exemplified by multienzyme cascade reactions as described in three recent articles by Park and coworkers [134,138,139]. In these sequential enzymatic reactions, the hydration step of either oleic acid by a ∆9 hydratase [139] or linoleic acid by a novel ∆12 hydratase [138] forms the starting point for multi branched enzymatic cascades.…”
Section: Fatty Acid Double Bond Hydratasesmentioning
confidence: 99%
See 1 more Smart Citation
“…AlkJ was applied before to catalyse the conversion of alcohols to aldehydes in E. coli 78,113,117 . This is the first report of its functionality on 9-hydroxy ethyl nonanoate.…”
Section: Discussionmentioning
confidence: 99%
“…AlkJ has received attention since it can produce the terminal aldehydes that can be converted to amines by ω-transaminases 117,141 . In twoliquid phase conversions with AlkBGTJL, the aldehyde and alcohol intermediates still accumulated.…”
Section: 42mentioning
confidence: 99%